Flexible Composite Carbon Films Prepared by a Pancake‐Making Method for Electromagnetic Interference Shielding. Issue 7 (18th February 2020) - Yang, Minglong; Wei, Qiang; Li, Jianjun; Wang, Yao; Guo, Hongfei; Gao, Liya; Huang, Li; He, Xiaodong; Li, Yibin; Yuan, Ye
Abstract: Inspired by the traditional Chinese "pancake‐making" method, the efficient electromagnetic interferences (EMI) shielding composite carbon films are conveniently obtained by assembling graphene oxide (GO) sheets, carbon nanotubes (CNTs), and Co/C nanocomposites into a laminated "nacre‐like" structure. The developed composite carbon films are characterized by a shielding effectiveness (SE) up to ≈51 dB in X band with a small thickness of ≈34.3 µm. Moreover, the composite carbon film shows favorable flexibility and the SE values almost keep a constant after repeatedly bending test. These results demonstrate a promising approach to simply fabricate a flexible and highly efficient EMI shielding material. Abstract : Inspired by the traditional Chinese "pancake‐making" method, the efficient electromagnetic interferences (EMI) shielding composite carbon films are conveniently obtained by assembling graphene oxide (GO) sheets, carbon nanotubes (CNTs) and Co/C nanocomposites into a laminated "nacre‐like" structure. The EMI shielding values almost keep a constant after repeatedly bending test, which demonstrate a promising approach to simply fabricate a flexible and highly efficient EMI shielding material.